EFFECTIVENESS OF RETROWALKING AND FORWARD WALKING TREADMILL TRAINING ON LEVEL OF C-REACTIVE PROTEIN AND ABDOMINAL ADIPOSITY IN UNTRAINED YOUNG ADULTS: PROTOCOL FOR A COMPARATIVE STUDY (International Journal of Physiotherapy, 2019)
Background: Retro walking has been shown to require increased metabolic cost and cardiopulmonary demand compared with forward walking at the same speeds. Levels of C reactive protein and abdominal adiposity are related directly to the risk of cardiovascular disease. The study aims to compare the effect of retro walking treadmill training and that of forward walking treadmill training on C-reactive protein levels and abdominal adiposity in untrained young adults.Methods: In this comparative experimental study, 250 participants will be recruited by using purposive sampling and allocated randomly to two groups. One group will undergo retro walking treadmill training for five sessions a week for six weeks, and the other group will undergo forward walking treadmill training for the same period. The waist-hip ratio will be calculated, and blood samples to measure CRP levels will be taken before and after the 6-week intervention.Results: The data will be tabulated and subjected to statistical analysis, by the paired and unpaired t-tests and the Wilcoxon Signed Rank test.Conclusion: To our knowledge, it is the first experimental study to compare the effect of retro walking treadmill training and forward walking treadmill training on C-reactive protein levels and abdominal adiposity in untrained young adults. The results of the study will throw light on which type of training, to what extent, might help lower cardiovascular4risk in young adults.